Yellow micro-arc oxidation electrolyte and preparation and use methods thereof

By optimizing the formulation and treatment methods of microarc oxidation electrolyte, the problem of improving material uniformity and performance in traditional microarc oxidation treatment is solved, and the density and corrosion resistance of the yellow ceramic film layer on the surface of magnesium alloy is improved, satisfying the aesthetics and performance requirements.

CN119265664AInactive Publication Date: 2025-01-07ANHUI MUYI TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411809050.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

On the basis of ensuring uniform coloration of the material, traditional microarc oxidation treatment is difficult to simultaneously improve the corrosion resistance and mechanical properties of magnesium alloy materials, and the acidic environment of the existing electrolyte inhibits the formation of crystalline MgO with good density.

Method used

By optimizing the formulation of microarc oxidation electrolyte, NaAlO2, Na2SiO3, C6H5Na3O7, EDTA-2Na, KMnO4 and H2O2 are added to adjust the pH value of the electrolyte to 10.0, high-speed stirring and ultrasonic oscillation are used to form a stable aqueous solution. Microarc oxidation treatment on the surface of magnesium alloy.

Benefits of technology

The magnesium alloy surface has achieved a yellow ceramic film layer with uniform color, smooth surface and denseness, which improves wear resistance and corrosion resistance, and ensures the stability and environmental protection of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of material surface treatment, in particular to a yellow micro-arc oxidation electrolyte and a preparation and use method thereof. According to the yellow micro-arc oxidation electrolyte, NaAlO2, Na2SiO3, C6H5Na3O7, EDTA-2Na, KMnO4, H2O2, NaOH and other components are compounded with deionized water, and the alkaline electrolyte is formed through mixing, stirring and ultrasonic treatment. By optimizing the formula of the electrolyte, the limitation that a traditional micro-arc oxidation film layer is single in color is overcome, and color diversification is successfully achieved. The electrolyte is adopted for micro-arc oxidation treatment, a uniform yellow ceramic film layer can be formed on the surface of the magnesium alloy, and the film layer has good surface smoothness, compactness, wear resistance and corrosion resistance and excellent stability. Compared with a traditional process, the method has the advantages that the attractiveness and functionality of the film layer are improved, the performance of the surface of the magnesium alloy is greatly improved, and the magnesium alloy has better applicability and market prospects in wider industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material surface treatment, and in particular to a yellow micro-arc oxidation electrolyte and a preparation and use method thereof. Background Art

[0002] Micro-arc oxidation is developed on the basis of traditional anodizing technology. It is a surface treatment technology that directly generates ceramic oxide film in situ on the surface of valve metals such as A1, Mg, and Ti. Aluminum, magnesium, titanium and other alloy materials are used as 3C body structural parts, especially the shells of laptops and mobile phones. They require not only high surface hardness and good wear resistance, but also a gorgeous and exquisite appearance. The use of micro-arc oxidation coloring treatment can generate a layer of colored film with good wear resistance on the alloy surface.

[0003] Traditional micro-arc oxidation treatment can effectively improve the wear resistance and hardness of the alloy material surface, and can also improve the corrosion resistance to a certain extent. However, on this basis, micro-arc oxidation treatment also needs to ensure good coloring of the material to improve the aesthetic effect of the material. Therefore, how to ensure good corrosion resistance and mechanical properties while ensuring uniform coloring of the material is an important research direction of non-ferrous micro-arc oxidation treatment at this stage. On this basis, the optimization of the electrolyte is objectively important.

[0004] Chinese patent CN101914765B discloses a method for preparing a dark ceramic film by chemical conversion of magnesium alloy and micro-arc oxidation, wherein AM50 magnesium alloy is first chemically converted and then micro-arc oxidized to obtain a yellowish-brown micro-arc oxidation ceramic film, and the micro-arc oxidation electrolyte is: 8-12g / L sodium aluminate + sodium phosphate (sodium aluminate: sodium phosphate = 5:5). The yellow ceramic film prepared by the above method is too light in color, too thin in thickness, and not dense enough. Because the acidic pH of the electrolyte has an inhibitory effect on the formation of the micro-arc oxidation film, the Mg and O atoms do not have enough time to arrange regularly in the acidic environment during the film formation process, so that crystalline MgO with good density cannot be obtained. Moreover, the dissolution rate of the passivation film is very fast under acidic conditions, so that the micro-arc discharge cannot proceed smoothly. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a gradual micro-arc oxidation preparation method, which breaks the limitation of the traditional film layer's single color by optimizing the formula of the micro-arc oxidation electrolyte, realizes the advantage of color diversity, and obtains a yellow ceramic film layer with uniform color, smooth surface, good density, wear resistance, corrosion resistance and good stability on the surface of the magnesium alloy.

[0006] To achieve the above purpose, the technical solution adopted is: In a first aspect, the present invention provides a yellow micro-arc oxidation electrolyte, wherein the electrolyte is an aqueous solution, and the aqueous solution comprises the following components: NaAlO2, Na2SiO3, C6H5Na3O7, EDTA-2Na, KMnO4, H2O2 and NaOH.

[0007] According to the yellow micro-arc oxidation electrolyte of the present invention, further, the concentration content of various components in the aqueous solution is as follows: NaAlO2: 15-45g / L; NaOH: 1-3.5g / L; Na2SiO3: 0.1g / L; C6H5Na3O7: 0.1-0.4g / L; EDTA-2Na: 2-5g / L; KMnO4: 1-3g / L; H2O2: 5-25ML / L.

[0008] In a second aspect, the present invention further provides a method for preparing a yellow micro-arc oxidation electrolyte, which is used for preparing the above-mentioned yellow micro-arc oxidation electrolyte, comprising the following steps: S11. NaAlO2, Na2SiO3, C6H5Na3O7 and EDTA-2Na were added to deionized water, stirred and allowed to stand for 30 min to obtain a mixed solution; S12. KMnO4 was added to the mixed solution, and H2O2 was added after high-speed stirring and ultrasonic vibration was uniformly performed, and a yellow micro-arc oxidation electrolyte was obtained after standing; S13. Add NaOH to the mixed solution, adjust the pH value of the mixed solution to 10.0, and obtain a yellow micro-arc oxidation electrolyte after standing.

[0009] According to the method for preparing a yellow micro-arc oxidation electrolyte of the present invention, further, in step S12, the rotation speed of the high-speed stirring is 1000-1400 r / min, and the stirring time is 8-10 min.

[0010] According to the method for preparing a yellow micro-arc oxidation electrolyte of the present invention, further, in step S12, the ultrasonic oscillation method is to oscillate for 15-25 minutes at an ultrasonic power of 800 W.

[0011] In a third aspect, a method for using a yellow micro-arc oxidation electrolyte is also provided, which is used for the specific use of the above-mentioned yellow micro-arc oxidation electrolyte, and is characterized in that it comprises the following steps: S21. Sample surface pretreatment: polish the sample surface with sandpaper, then clean and dry it with ultrasound; S22. Micro-arc oxidation: Place the sample in a yellow micro-arc oxidation electrolyte and perform micro-arc oxidation on the sample using an AC pulse power supply; S23. Impurity cleaning: remove the sample from the yellow micro-arc oxidation electrolyte and wash with deionized water; S24. Soak the sample in distilled water for 10 to 15 minutes and dry it to obtain a sample with a yellow micro-arc oxidation ceramic film on the surface.

[0012] According to the method for using the yellow micro-arc oxidation electrolyte of the present invention, further, the sample is an AZ31B magnesium alloy substrate.

[0013] According to the method for using the yellow micro-arc oxidation electrolyte of the present invention, further, in step S22, the micro-arc oxidation treatment process is specifically to set the current density to 8-15A / dm 2 , the forward voltage is 380-400V, the negative voltage is 20-200V, the pulse frequency is 600-900Hz, the duty cycle is 15%-50%, and the oxidation time is 60min.

[0014] According to the method for using the yellow micro-arc oxidation electrolyte of the present invention, further, in step S22, when the micro-arc oxidation treatment is performed, the temperature of the yellow micro-arc oxidation electrolyte is 25-40°C.

[0015] According to the method for using the yellow micro-arc oxidation electrolyte of the present invention, further, in step S22, when performing the micro-arc oxidation treatment, a magnesium alloy is used as an anode and a stainless steel sheet is used as a cathode.

[0016] The beneficial effects achieved by adopting the above technical solution are: 1. The electrolyte has a reasonable composition configuration, using sodium aluminate (NaAlO2), sodium silicate (Na2SiO3), sodium citrate (C6H5Na3O7), disodium ethylenediaminetetraacetic acid (EDTA-2Na) and other chemical reagents, which can effectively improve the electrochemical stability of the electrolyte and ensure stable operation during the micro-arc oxidation process. Especially under high voltage and high temperature conditions, the electrolyte can maintain good performance and is not prone to hydrogen precipitation or deposition; 2. By adding potassium permanganate (KMnO4) and hydrogen peroxide (H2O2) to the electrolyte, the quality of the oxide film can be effectively improved. Potassium permanganate can act as an oxidant to enhance the density and wear resistance of the oxide film, while hydrogen peroxide helps to improve the glossiness and surface uniformity of the film, thereby making the oxide film have better corrosion resistance and aesthetics; 3. The electrolyte formula does not contain toxic or difficult-to-degrade chemicals, and will not cause serious pollution to the environment during use. By optimizing the composition of the electrolyte, it not only improves the effect of micro-arc oxidation, but also meets the requirements of green environmental protection and adapts to the current demand for environmental protection treatment processes; 4. The preparation method of the present invention is simple and easy to implement. A yellow micro-arc oxidation electrolyte that meets the requirements can be prepared through simple chemical reaction control, thereby reducing production costs and improving process operability.

[0017] In general, the preparation method of the present invention is simple and has a wide range of applications, and is applicable to light metals such as magnesium alloys. The prepared yellow ceramic film has the advantages of uniform color, smooth surface, good density, high wear resistance, good corrosion resistance, and good stability. DETAILED DESCRIPTION

[0018] The following is a clear and complete description of the exemplary embodiments of the present invention. Unless otherwise defined, the technical or scientific terms used in the present invention should have the common meanings understood by people with ordinary skills in the field.

[0019] Example 1

[0020] ① Sample preparation: Using AZ31B magnesium alloy matrix, the size of the AZ31B magnesium alloy matrix was cut into samples of 15 mm × 15 mm × 4 mm; a. Surface grinding: Use 360#, 500#, and 800# water sandpaper to grind the magnesium alloy matrix samples in turn to remove surface burrs and oxide layers to ensure that the surface of the magnesium alloy matrix is ​​flat and smooth.

[0021] b. Cleaning treatment: After the surface of the magnesium alloy substrate is polished, the surface of the magnesium alloy substrate is thoroughly cleaned with deionized water, and ultrasonically cleaned in an 800W ultrasonic environment for 10 minutes, then the magnesium alloy substrate is taken out and rinsed again, and the surface moisture is dried at a constant temperature of 55°C.

[0022] ②Prepare electrolyte: a. Add sodium aluminate (NaAlO2) to deionized water and stir with a glass rod until it is completely dissolved to ensure that sodium aluminate provides sufficient aluminum ions for the formation of the oxide film; b. Add sodium silicate (Na2SiO3) to adjust the stability of the electrolyte. Sodium silicate helps maintain the electrochemical stability of the electrolyte by adjusting the ionic strength of the solution, preventing unnecessary chemical reactions or precipitation in the solution, and ensuring the smooth progress of the micro-arc oxidation process; In this step, the solution needs to be stirred continuously to ensure uniform mixing of the solution; c. Add sodium citrate (C6H5Na3O7) and disodium ethylenediaminetetraacetate (EDTA-2Na). Sodium citrate (C6H5Na3O7) and disodium ethylenediaminetetraacetate (EDTA-2Na) as complexing agents help stabilize the metal ions in the solution, prevent uneven oxide film on the surface of the magnesium alloy matrix, and help improve the adhesion and density of the film layer; In this step, the solution needs to be stirred continuously to ensure uniform mixing of the solution; then, the solution is allowed to stand for 30 minutes; d. Add potassium permanganate (KMnO4) to enhance the density and surface hardness of the oxide film and improve the structure of the film through the oxidation of potassium permanganate; In this step, the solution needs to be stirred with a high-speed stirrer until the solution is mixed evenly; e. Add hydrogen peroxide (H2O2), which acts as an oxidant to further improve the oxidizing ability of the electrolyte, promote the oxidation reaction, and increase the gloss and surface smoothness of the oxide film; In this step, the solution is shaken by an ultrasonic oscillator until the solution is mixed uniformly; f. Finally, sodium hydroxide (NaOH) is added to adjust the pH of the solution to 10.0 to ensure that the electrolyte maintains appropriate alkalinity to promote the growth of the oxide film.

[0023] The concentrations of the various components of the electrolyte finally configured in this embodiment 1 are specifically as follows: sodium aluminate (NaAlO2) is 15 g / L; sodium silicate (Na2SiO3) is 0.1 / L; sodium citrate (C6H5Na3O7) is 0.4 g / L; disodium ethylenediaminetetraacetic acid (EDTA-2Na) is 2 g / L; potassium permanganate (KMnO4) is 1 g / L; hydrogen peroxide (H2O2) is 10 ML / L; and sodium hydroxide (NaOH) is 1 g / L.

[0024] ③Micro-arc oxidation treatment a. Set up the electrolytic cell and electrodes: The cleaned and dried magnesium alloy substrate is used as an anode, and the stainless steel sheet is used as a cathode, and placed in the prepared electrolyte.

[0025] Ensure that the magnesium alloy matrix is ​​completely immersed in the electrolyte, and the electrolytic cell and power supply system should have good ventilation and cooling conditions to avoid excessive heat generation during the electrolysis process.

[0026] b. Use AC pulse power supply for micro-arc oxidation treatment. The specific power supply parameters are as follows: Current density: 8-15A / dm²; forward voltage: 380-400V; negative voltage: 20-200V; pulse frequency: 600-900Hz; duty cycle: 15%-50%; oxidation time: 60min.

[0027] c. Electrolytic reaction and film formation: Under the action of AC pulse power, aluminum ions in the electrolyte react with oxygen to form a yellow ceramic film layer on the surface of the magnesium alloy substrate.

[0028] d. Post-processing: After micro-arc oxidation treatment, the magnesium alloy substrate is removed and thoroughly cleaned with deionized water to remove residual electrolyte. The cleaned substrate is soaked in distilled water for 5-10 minutes to remove surface impurities. Finally, it is dried in a constant temperature oven at 55°C.

[0029] ④Quality inspection a.Hardness test: The hardness of the oxide film was tested using a Vickers hardness tester, and the microhardness value obtained was 1800HV, which proves that the film layer has a high hardness and good wear resistance.

[0030] b.Thickness detection: The thickness of the oxide film was measured using a film thickness gauge, and the film thickness was found to be 31.5µm.

[0031] Example 2

[0032] The main difference between Example 2 and Example 1 is that the concentrations of the components in the electrolyte are different.

[0033] ① Sample preparation: Using AZ31B magnesium alloy matrix, the size of the AZ31B magnesium alloy matrix was cut into samples of 40 mm × 25 mm × 3 mm; a. Surface grinding: Use 360#, 500#, and 800# water sandpaper to grind the magnesium alloy matrix samples in turn to remove surface burrs and oxide layers to ensure that the surface of the magnesium alloy matrix is ​​flat and smooth.

[0034] b. Cleaning treatment: After the surface of the magnesium alloy substrate is polished, the surface of the magnesium alloy substrate is thoroughly cleaned with deionized water, and ultrasonically cleaned in an 800W ultrasonic environment for 10 minutes, then the magnesium alloy substrate is taken out and rinsed again, and the surface moisture is dried at a constant temperature of 55°C.

[0035] ②Prepare electrolyte: a. Add sodium aluminate (NaAlO2) to deionized water and stir with a glass rod until it is completely dissolved to ensure that sodium aluminate provides sufficient aluminum ions for the formation of the oxide film; b. Add sodium silicate (Na2SiO3) to adjust the stability of the electrolyte. Sodium silicate helps maintain the electrochemical stability of the electrolyte by adjusting the ionic strength of the solution, preventing unnecessary chemical reactions or precipitation in the solution, and ensuring the smooth progress of the micro-arc oxidation process; In this step, the solution needs to be stirred continuously to ensure uniform mixing of the solution; c. Add sodium citrate (C6H5Na3O7) and disodium ethylenediaminetetraacetate (EDTA-2Na). Sodium citrate (C6H5Na3O7) and disodium ethylenediaminetetraacetate (EDTA-2Na) as complexing agents help stabilize the metal ions in the solution, prevent uneven oxide film on the surface of the magnesium alloy matrix, and help improve the adhesion and density of the film layer; In this step, the solution needs to be stirred continuously to ensure uniform mixing of the solution; then, the solution is allowed to stand for 30 minutes; d. Add potassium permanganate (KMnO4) to enhance the density and surface hardness of the oxide film and improve the structure of the film through the oxidation of potassium permanganate; In this step, the solution needs to be stirred with a high-speed stirrer until the solution is mixed evenly; e. Add hydrogen peroxide (H2O2), which acts as an oxidant to further improve the oxidizing ability of the electrolyte, promote the oxidation reaction, and increase the gloss and surface smoothness of the oxide film; In this step, the solution is shaken by an ultrasonic oscillator until the solution is mixed evenly; f. Finally, sodium hydroxide (NaOH) is added to adjust the pH of the solution to 10.0 to ensure that the electrolyte maintains appropriate alkalinity to promote the growth of the oxide film.

[0036] The concentrations of the various components of the electrolyte finally configured in this embodiment 2 are specifically as follows: sodium aluminate (NaAlO2) is 45 g / L; sodium silicate (Na2SiO3) is 0.1 g / L; sodium citrate (C6H5Na3O7) is 0.2 g / L; disodium ethylenediaminetetraacetic acid (EDTA-2Na) is 5 g / L; potassium permanganate (KMnO4) is 2 g / L; hydrogen peroxide (H2O2) is 15 ML / L; and sodium hydroxide (NaOH) is 3.5 g / L.

[0037] ③Micro-arc oxidation treatment a. Set up the electrolytic cell and electrodes: The cleaned and dried magnesium alloy substrate is used as an anode, and the stainless steel sheet is used as a cathode, and placed in the prepared electrolyte.

[0038] Ensure that the magnesium alloy matrix is ​​completely immersed in the electrolyte, and the electrolytic cell and power supply system should have good ventilation and cooling conditions to avoid excessive heat generation during the electrolysis process.

[0039] b. Use AC pulse power supply for micro-arc oxidation treatment. The specific power supply parameters are as follows: Current density: 10A / dm²; forward voltage: 380-400V; negative voltage: 20-200V; pulse frequency: 600-900Hz; duty cycle: 15%-50%; oxidation time: 65min.

[0040] c. Electrolytic reaction and film formation: Under the action of AC pulse power, aluminum ions in the electrolyte react with oxygen to form a yellow ceramic film layer on the surface of the magnesium alloy substrate.

[0041] d. Post-processing: After micro-arc oxidation treatment, the magnesium alloy substrate is removed and thoroughly cleaned with deionized water to remove residual electrolyte. The cleaned substrate is soaked in distilled water for 5-10 minutes to remove surface impurities. Finally, it is dried in a constant temperature oven at 55°C.

[0042] ④Quality inspection a.Hardness test: The hardness of the oxide film was tested using a Vickers hardness tester, and the microhardness value obtained was 1700 HV.

[0043] b.Thickness detection: The thickness of the oxide film was measured using a film thickness gauge, and the film thickness was found to be 28.6µm.

[0044] Example 3

[0045] The main difference between Example 3 and Example 1 is that the concentrations of the components in the electrolyte are different.

[0046] ① Sample preparation: Using AZ31B magnesium alloy matrix, the size of the AZ31B magnesium alloy matrix was cut into samples of 15 mm × 15 mm × 4 mm; a. Surface grinding: Use 360#, 500#, and 800# water sandpaper to grind the magnesium alloy matrix samples in turn to remove surface burrs and oxide layers to ensure that the surface of the magnesium alloy matrix is ​​flat and smooth.

[0047] b. Cleaning treatment: After the surface of the magnesium alloy substrate is polished, the surface of the magnesium alloy substrate is thoroughly cleaned with deionized water, and ultrasonically cleaned in an 800W ultrasonic environment for 10 minutes, then the magnesium alloy substrate is taken out and rinsed again, and the surface moisture is dried at a constant temperature of 55°C.

[0048] ②Prepare electrolyte: a. Add sodium aluminate (NaAlO2) to deionized water and stir with a glass rod until it is completely dissolved to ensure that sodium aluminate provides sufficient aluminum ions for the formation of the oxide film; b. Add sodium silicate (Na2SiO3) to adjust the stability of the electrolyte. Sodium silicate helps maintain the electrochemical stability of the electrolyte by adjusting the ionic strength of the solution, preventing unnecessary chemical reactions or precipitation in the solution, and ensuring the smooth progress of the micro-arc oxidation process; In this step, the solution needs to be stirred continuously to ensure uniform mixing of the solution; c. Add sodium citrate (C6H5Na3O7) and disodium ethylenediaminetetraacetate (EDTA-2Na). Sodium citrate (C6H5Na3O7) and disodium ethylenediaminetetraacetate (EDTA-2Na) as complexing agents help stabilize the metal ions in the solution, prevent uneven oxide film on the surface of the magnesium alloy matrix, and help improve the adhesion and density of the film layer; In this step, the solution needs to be stirred continuously to ensure uniform mixing of the solution; then, the solution is allowed to stand for 30 minutes; d. Add potassium permanganate (KMnO4) to enhance the density and surface hardness of the oxide film and improve the structure of the film through the oxidation of potassium permanganate; In this step, the solution needs to be stirred with a high-speed stirrer until the solution is mixed evenly; e. Add hydrogen peroxide (H2O2), which acts as an oxidant to further improve the oxidizing ability of the electrolyte, promote the oxidation reaction, and increase the gloss and surface smoothness of the oxide film; In this step, the solution is shaken by an ultrasonic oscillator until the solution is mixed uniformly; f. Finally, add NaOH (sodium hydroxide) to adjust the pH of the solution to 10.0 to ensure that the electrolyte maintains appropriate alkalinity to promote the growth of the oxide film.

[0049] The concentrations of the various components of the electrolyte finally configured in this embodiment 3 are as follows: sodium aluminate (NaAlO2) is 25 g / L; sodium silicate (Na2SiO3) is 0.1 g / L; sodium citrate (C6H5Na3O7) is 0.3 g / L; disodium ethylenediaminetetraacetic acid (EDTA-2Na) is 3 g / L; potassium permanganate (KMnO4) is 2 g / L; hydrogen peroxide (H2O2) is 15 ML / L; and NaOH (sodium hydroxide) is 2 g / L.

[0050] ③Micro-arc oxidation treatment a. Set up the electrolytic cell and electrodes: The cleaned and dried magnesium alloy substrate is used as an anode, and the stainless steel sheet is used as a cathode, and placed in the prepared electrolyte.

[0051] Ensure that the magnesium alloy matrix is ​​completely immersed in the electrolyte, and the electrolytic cell and power supply system should have good ventilation and cooling conditions to avoid excessive heat generation during the electrolysis process.

[0052] b. Use AC pulse power supply for micro-arc oxidation treatment. The specific power supply parameters are as follows: Current density: 12A / dm²; forward voltage: 380-400V; negative voltage: 20-200V; pulse frequency: 600-900Hz; duty cycle: 15%-50%; oxidation time: 60min.

[0053] c. Electrolytic reaction and film formation: Under the action of AC pulse power, aluminum ions in the electrolyte react with oxygen to form a yellow ceramic film layer on the surface of the magnesium alloy substrate.

[0054] d. Post-processing: After micro-arc oxidation treatment, the magnesium alloy substrate is removed and thoroughly cleaned with deionized water to remove residual electrolyte. The cleaned substrate is soaked in distilled water for 5-10 minutes to remove surface impurities. Finally, it is dried in a constant temperature oven at 55°C.

[0055] ④Quality inspection a.Hardness test: The hardness of the oxide film was tested using a Vickers hardness tester, and the microhardness value obtained was 1500HV, which proves that the film layer has a high hardness and good wear resistance.

[0056] b.Thickness detection: The thickness of the oxide film was measured using a film thickness gauge, and the film thickness was found to be 26.3µm.

[0057] Comparative Example 1

[0058] The main difference between the comparative example and Examples 1-3 is that the concentrations of the components in the electrolyte are different and the micro-arc oxidation time is different; and the concentrations of the components in the electrolyte and the micro-arc oxidation time of the comparative example are not within the scope of protection of the present invention.

[0059] ① Sample preparation: Using AZ31B magnesium alloy matrix, the size of the AZ31B magnesium alloy matrix was cut into samples of 40 mm × 25 mm × 3 mm; a. Surface grinding: Use 360#, 500#, and 800# water sandpaper to grind the magnesium alloy matrix samples in turn to remove surface burrs and oxide layers to ensure that the surface of the magnesium alloy matrix is ​​flat and smooth.

[0060] b. Cleaning treatment: After the surface of the magnesium alloy substrate is polished, the surface of the magnesium alloy substrate is thoroughly cleaned with deionized water, and ultrasonically cleaned in an 800W ultrasonic environment for 10 minutes, then the magnesium alloy substrate is taken out and rinsed again, and the surface moisture is dried at a constant temperature of 55°C.

[0061] ②Prepare electrolyte: a. Add sodium aluminate (NaAlO2) to deionized water and stir with a glass rod until it is completely dissolved to ensure that sodium aluminate provides sufficient aluminum ions for the formation of the oxide film; b. Add sodium silicate (Na2SiO3) to adjust the stability of the electrolyte. Sodium silicate helps maintain the electrochemical stability of the electrolyte by adjusting the ionic strength of the solution, preventing unnecessary chemical reactions or precipitation in the solution, and ensuring the smooth progress of the micro-arc oxidation process; In this step, the solution needs to be stirred continuously to ensure uniform mixing of the solution; c. Add sodium citrate (C6H5Na3O7) and disodium ethylenediaminetetraacetate (EDTA-2Na). Sodium citrate (C6H5Na3O7) and disodium ethylenediaminetetraacetate (EDTA-2Na) as complexing agents help stabilize the metal ions in the solution, prevent uneven oxide film on the surface of the magnesium alloy matrix, and help improve the adhesion and density of the film layer; In this step, the solution needs to be stirred continuously to ensure uniform mixing of the solution; then, the solution is allowed to stand for 30 minutes; d. Add potassium permanganate (KMnO4) to enhance the density and surface hardness of the oxide film and improve the structure of the film through the oxidation of potassium permanganate; In this step, the solution needs to be stirred with a high-speed stirrer until the solution is mixed evenly; e. Add hydrogen peroxide (H2O2), which acts as an oxidant to further improve the oxidizing ability of the electrolyte, promote the oxidation reaction, and increase the gloss and surface smoothness of the oxide film; In this step, the solution is shaken by an ultrasonic oscillator until the solution is mixed evenly; f. Finally, add NaOH (sodium hydroxide) to adjust the pH of the solution to 10.0 to ensure that the electrolyte maintains appropriate alkalinity to promote the growth of the oxide film.

[0062] The concentrations of the various components of the electrolyte finally configured in this comparative example are as follows: sodium aluminate (NaAlO2) is 5 g / L; sodium silicate (Na2SiO3) is 0.5 g / L; sodium citrate (C6H5Na3O7) is 0.6 g / L; disodium ethylenediaminetetraacetic acid (EDTA-2Na) is 8 g / L; potassium permanganate (KMnO4) is 1 g / L; and hydrogen peroxide (H2O2) is 2 ML / L.

[0063] ③Micro-arc oxidation treatment a. Set up the electrolytic cell and electrodes: The cleaned and dried magnesium alloy substrate is used as an anode, and the stainless steel sheet is used as a cathode, and placed in the prepared electrolyte.

[0064] Ensure that the magnesium alloy matrix is ​​completely immersed in the electrolyte, and the electrolytic cell and power supply system should have good ventilation and cooling conditions to avoid excessive heat generation during the electrolysis process.

[0065] b. Use AC pulse power supply for micro-arc oxidation treatment. The specific power supply parameters are as follows: Current density: 10A / dm²; forward voltage: 380-400V; negative voltage: 20-200V; pulse frequency: 600-900Hz; duty cycle: 15%-50%; oxidation time: 30min.

[0066] c. Electrolytic reaction and film formation: Under the action of AC pulse power, aluminum ions in the electrolyte react with oxygen to form a yellow ceramic film layer on the surface of the magnesium alloy substrate.

[0067] d. Post-processing: After micro-arc oxidation treatment, the magnesium alloy substrate is removed and thoroughly cleaned with deionized water to remove residual electrolyte. The cleaned substrate is soaked in distilled water for 5-10 minutes to remove surface impurities. Finally, it is dried in a constant temperature oven at 55°C.

[0068] ④Quality inspection a.Hardness test: The hardness of the oxide film was tested using a Vickers hardness tester, and the microhardness value obtained was 800HV, which proves that the film layer has a high hardness and good wear resistance.

[0069] b.Thickness detection: The thickness of the oxide film was measured using a film thickness gauge, and the film thickness was found to be 15.0 µm.

[0070] The thickness of the ceramic layer on the surface of each group of samples was tested. At the same time, 3 points on the surface of each group of samples were selected and hardness tested using a Vickers hardness tester. The specific results are shown in Table 1 below: Table 1: Vickers hardness test results of various embodiments and comparative examples

[0071] According to the standard JB / T6073-92 (full immersion corrosion test of metal covering layer), the corrosion resistance of the magnesium alloy matrix samples after oxidation treatment in each embodiment and comparative example was tested. The magnesium alloy matrix sample was fully immersed in a 3.5% NaCl solution. The mass of the magnesium alloy matrix sample before immersion was m1, and the mass of the magnesium alloy matrix sample after immersion was m2. M=m1-m2 is the weight of the immersion weight loss. The more weight loss, the more serious the corrosion. The weight loss of each embodiment and comparative example sample at different immersion times was recorded. The specific results are shown in Table 2 below: Table 2: Corrosion test results of various embodiments and comparative examples

[0072] It can be seen from the detection of Table 1 and Table 2 that the yellow ceramic film layer on the surface of the magnesium alloy substrate in Examples 1-3 has better mechanical properties and corrosion resistance.

[0073] The preferred embodiments for implementing the present invention have been described in detail above, but it should be understood that the role of these embodiments is only to exemplify, and is not intended to limit the scope, applicability or configuration of the present invention in any way. The protection scope of the present invention is defined by the attached claims and their equivalents. A person of ordinary skill in the art can make many changes to the above embodiments under the guidance of the present invention, and these changes all fall within the protection scope of the present invention.

Claims

1. A yellow micro-arc oxidation electrolyte, characterized in that: The electrolyte is an aqueous solution, and the aqueous solution includes the following components: NaAlO2, Na2SiO3, C6H5Na3O7, EDTA-2Na, KMnO4, H2O2 and NaOH.

2. The yellow micro-arc oxidation electrolyte according to claim 1, characterized in that: The concentrations of various components in the aqueous solution are as follows: NaAlO2: 15-45 g / L; NaOH: 1-3.5 g / L; Na2SiO3: 0.1 g / L; C6H5Na3O7: 0.1-0.4 g / L; EDTA-2Na: 2-5 g / L; KMnO4: 1-3 g / L; H2O2: 5-25 ML / L.

3. A method for preparing a yellow micro-arc oxidation electrolyte, used for preparing the yellow micro-arc oxidation electrolyte as claimed in claim 1 or 2, characterized in that: The following steps are involved: S11. NaAlO2, Na2SiO3, C6H5Na3O7 and EDTA-2Na were added to deionized water, stirred and allowed to stand for 30 min to obtain a mixed solution; S12. KMnO4 was added to the mixed solution, and H2O2 was added after high-speed stirring and ultrasonic shaking; S13. Add NaOH to the mixed solution, adjust the pH value of the mixed solution to 10.0, and obtain a yellow micro-arc oxidation electrolyte after standing.

4. The method for preparing the yellow micro-arc oxidation electrolyte according to claim 3, characterized in that: In step S12, the rotation speed of high-speed stirring is 1000-1400 r / min, and the stirring time is 8-10 min.

5. The method for preparing the yellow micro-arc oxidation electrolyte according to claim 3, characterized in that: In step S12, the ultrasonic oscillation method is to oscillate at an ultrasonic power of 800 W for 15-25 minutes.

6. A method for using a yellow micro-arc oxidation electrolyte, for the specific use of the yellow micro-arc oxidation electrolyte as claimed in claim 1 or 2, characterized in that: The following steps are involved: S21. Sample surface pretreatment: polish the sample surface with sandpaper, then clean and dry it with ultrasound; S22. Micro-arc oxidation: Place the sample in a yellow micro-arc oxidation electrolyte and perform micro-arc oxidation on the sample using an AC pulse power supply; S23. Impurity cleaning: remove the sample from the yellow micro-arc oxidation electrolyte and wash with deionized water; S24. Soak the sample in distilled water for 10 to 15 minutes and dry it to obtain a sample with a yellow micro-arc oxidation ceramic film on the surface.

7. The method for using the yellow micro-arc oxidation electrolyte according to claim 6, characterized in that: The sample is an AZ31B magnesium alloy substrate.

8. The method for using the yellow micro-arc oxidation electrolyte according to claim 6, characterized in that: In step S22, the micro-arc oxidation process is specifically to set the current density to 8-15A / dm 2 , the forward voltage is 380-400V, the negative voltage is 20-200V, the pulse frequency is 600-900Hz, the duty cycle is 15%-50%, and the oxidation time is 60-65min.

9. The method for using the yellow micro-arc oxidation electrolyte according to claim 6, characterized in that: In step S22, when the micro-arc oxidation treatment is performed, the temperature of the yellow micro-arc oxidation electrolyte is 25-40°C.

10. The method for using the yellow micro-arc oxidation electrolyte according to claim 6, characterized in that: In step S22, when performing the micro-arc oxidation treatment, a magnesium alloy is used as an anode and a stainless steel sheet is used as a cathode.

Citation Information

Patent Citations

  • In-situ growth method of yellow ceramic coating on TC4 titanium alloy surface

    CN103320838A

  • Method for preparing magnesium alloy with micro-arc oxidation ceramic membrane

    CN103614762A

  • Preparation method of yellow corrosion-resistant ceramic membrane grown in situ on surface of aluminum matrix composite material

    CN110257880A

  • AF coating method

    CN116926464A

  • Oxide coating on magnesium alloy with anti-corrosion and anti-microbial properties and Manufacturing method thereof

    KR1020100119594A